Manajemen Sumber Daya Manusia Di Bank Syariah: Tantangan dan Peluang Dalam Era Digital - Ardista, Rini; Kusuma, Aditya Putra; Munandar, Asep Nur Imam (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to identify the key opportunities and challenges faced by human resource management (HRM) in Islamic banks in addressing the digital era. The research employs a literature review method to evaluate various sources relevant to this topic. The findings reveal that the rapid digitization in the banking industry has created new requirements, including the need to enhance digital competencies among staff. These digital skills are crucial for employees to adapt to continuously evolving systems and technologies. The main challenge is the need to upskill and retrain the workforce to equip them with the necessary expertise to operate the digital technologies used in banking operations. HRM must ensure that employees possess relevant technical skills, analytical abilities, and the capability to quickly adapt to technological changes. This process requires significant resource allocation for the continuous education and skill development of employees. Digital transformation brings changes to the work culture in Islamic banks. The implementation of digital technology fosters a more flexible and collaborative work environment, which in turn affects the composition and dynamics of work teams. The recruitment process also needs adjustments to attract talent with digital competencies who can quickly adapt to technological advancements. Islamic banks should seek candidates who not only possess technical skills but also adhere to Sharia values. In the other hand, employee retention strategies should include attractive career development programs and competitive incentives to retain top talent.